A study of the Impact of Locus of Control and Conformity on Creativity: Gender Differences among Malaysian Undergraduates - Chin, Chun Yuin; Lim, Phylicia Hui Tung; Soh, Sei Ern (2021)
Creativity becomes an important feature in this era of creativity, especially in education and the workplace. Creativity has become one of the main issues of unemployment of undergraduates in Malaysia. The present study was aimed to study the impact of LOC, conformity on creativity among Malaysian undergraduates. This study was also aimed to study the gender difference in LOC, conformity and creativity among Malaysian undergraduates. Cross-sectional research design was used in this study. A total of 393 Malaysian undergraduates aged 18 to 26 years who were studying in public or private universities in Malaysia were recruited through the convenience sampling method. Data was collected by using Qualtrics and distributed online through social media. The Rotter’s Internal-External Locus of Control Scale, Mehrabian Conformity Scale, and modified version of Self-Rated Creativity Scale were used as the measurement for this study. Results of correlation analysis showed that there was a significant negative correlation between LOC and creativity and a significant positive correlation between conformity and creativity. Besides, the results of regression analysis indicated that LOC and conformity significantly predicted creativity. However, independent t-test showed no significant gender difference in LOC, conformity, and creativity. Theoretically, the present study provided the references for future researchers to further exploration of the relevant study. In terms of practical implication, the present study may help educators develop related programs to assist undergraduates in equipping creative thinking skills. For future studies, it is recommended that a probability sampling method can be conducted to further enhance the accuracy of the findings.